Risk of pancreatic cancer by alcohol dose, duration, and pattern of consumption, including binge drinking: a population-based study - Gupta, Samir (Springer Netherlands, 2010)
Alcohol consumption is postulated to be a risk factor for pancreatic cancer (PCA), but clarification of degree of risk related to consumption characteristics is lacking. We examined the association between alcohol consumption and PCA in a population-based case–control study (532 cases, 1,701 controls) in the San Francisco Bay Area. Population-based controls were frequency-matched by sex, age within 5-year categories and county of residence to cases identified by the cancer registry’s rapid case ascertainment. Detailed alcohol consumption data, including binge drinking (≥5 drinks/day), were collected during in-person interviews. Odds ratios (OR) and 95% confidence intervals (95% CI) were computed using adjusted unconditional logistic regression. Depending on dose, duration, and pattern of drinking, ORs were increased 1.5- to 6-fold among men but not women. In men, ORs increased with increasing overall alcohol consumption (22–35 drinks/week OR = 2.2, 95% CI = 1.1–4.0; ≥35 drinks/week OR = 2.6, 95% CI = 1.3–5.1, p-trend = 0.04). Most notable were effects with a history of binge drinking (OR = 3.5, 95% CI = 1.6–7.5) including increased number of drinks per day (p-trend = 0.002), and increased years of binge drinking (p-trend = 0.0006). In fully adjusted models that included smoking and other confounders, ORs for binge drinking in men were somewhat higher than in age-adjusted models. Results from our detailed analyses provide support for heavy alcohol consumption (including binge drinking) as a risk factor for PCA in men.